2020
DOI: 10.1371/journal.pone.0232141
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of time frame binning for FDOPA uptake quantification in glioma

Abstract: Introduction 3,4-dihydroxy-6-[18F]fluoro-L-phenylalanine (FDOPA) uptake quantification in glioma assessment can be distorted using a non-optimal time frame binning of time-activity curves (TAC). Under-sampling or over-sampling dynamic PET images induces significant variations on kinetic parameters quantification. We aimed to optimize temporal time frame binning for dynamic FDOPA PET imaging. Methods Fourteen patients with 33 tumoral TAC with biopsy-proven gliomas were analysed. The mean SUVmax tumor-to-brain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Still, three main applicability concerns remain due to the use of carbidopa for some patients, the combination with MRI in cases of no radiotracer uptake (17% in this study) and a selection bias (patients were included only if both molecular data were known and a dynamic PET acquisition had been made). Moreover, it is worth noting that a recent study reported by Girard et al sought to improve the time frame binning for dynamic 18 F-FDOPA PET imaging [ 33 ]. The authors used a three-compartment model, which is the most commonly used for full kinetic analysis of PET, and compared five different time samplings in 14 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Still, three main applicability concerns remain due to the use of carbidopa for some patients, the combination with MRI in cases of no radiotracer uptake (17% in this study) and a selection bias (patients were included only if both molecular data were known and a dynamic PET acquisition had been made). Moreover, it is worth noting that a recent study reported by Girard et al sought to improve the time frame binning for dynamic 18 F-FDOPA PET imaging [ 33 ]. The authors used a three-compartment model, which is the most commonly used for full kinetic analysis of PET, and compared five different time samplings in 14 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Voxel size (XYZ) was 1×1×2 mm 3 . From the bolus arrival time, a 0-20-min static and dynamic (8×15 sec, 2×30 sec, 2×60 sec, 3×300 sec) series were reconstructed (18).…”
Section: Pet/ct Imaging Protocolmentioning
confidence: 99%
“…SUVmax and SUVmean were respectively the maximum and the mean of the SUVs of the VOI. The reversible single-tissue compartment model with blood volume parameter (with K1 = rate constant from blood to tissue, k2 = rate constant from the tissue compartment to the arterial blood) was used to extract kinetic parameters (PMOD software version 3.8; PMOD Technologies; Zürich, Switzerland) (18).…”
Section: Image Analysismentioning
confidence: 99%
“…Voxel size (XYZ) was 1 × 1 × 2 mm 3 . A 20-min static image 10 min after injection in accordance with current recommendations (23) and an optimal dynamic time sampling of 8 × 15 s-−2 × 30 s-−2 × 60 s-−3 × 300 s from the bolus arrival time (24) were reconstructed from a 40-min list-mode acquisition immediately after FDOPA injection.…”
Section: Pet/ct Imaging Protocolmentioning
confidence: 99%